Simultaneous Volar and Dorsal Dislocation of Proximal Inter Phalangeal Joints in Adjacent Fingers - A Case Report - Sabapathy, S Raja; Bose, Vijay C; Rex, C; Dheenadhayalan, J (Indian Journal of Plastic Surgery, 1994)
Volar dislocation of PIP joint or MCP joint is a rare injury. They are seldom seen acutely and hence literature is sparse on the ideal method of management of these injuries. We had a patient who presented with a rare combination of volar dislocations of PIP and MCP joints of the ring finger with a classic dorsal dislocation of the PIP joint of the little finger. All dislocations underwent successful closed reduction in the acute stage followed by appropriate method of immobilisation and physiotherapy.